Uso de alumininosilicato clinoptilolita (ZeoterA) en el cultivo de frijol (Phaseolus vulgaris) controlando antracnosis (Colletotrichum lindemuthianum) bajo diferentes dosis de fósforo - Pazmiño Muñoz, Edison Marcelo (2023)
Anthracnose, caused by Colletotrichum lindemuthianum, is one of the most important seed-borne diseases of the common bean (Phaseolus vulgaris L.). The disease is prevalent in areas experiencing cool, wet weather conditions, causing up to 100% yield loss. The objective of this research was to evaluate the use of clinoptilolite aluminosilicate (ZeoterA) in the cultivation of beans (Phaseolus vulgaris) controlling anthracnose (Colletotrichum lindemuthianum) under different doses of phosphorus. The design used was Completely Randomized Blocks (DBCA) where there were 6 treatments with different doses of ZeoterA. They were divided into two applications of fertilizers and ZeoterA during the trial and different agronomic and yield variables were evaluated. An economic analysis of the treatments was carried out according to the level of yield.